Physa mezzalirai, a new cretaceous basommatophoran from Adamantina formation, Brazil. - Ghilardi, Renato Pirani [UNESP]; Carbonaro, Fabio A.; Simone, Luiz Ricardo L. (My University, 2011)
This paper deals with a formal description of Physa mezzalirai (Basommatophora, Physidae), a new species of freshwater gastropod that lived in upper Cretaceous deposits, in sand-silty beds of Adamantina formation, Bauru basin, from Marlia, São Paulo state, Brazil. This formal description legitimates the availability of the name previously described in 2010 by same authors; being this paper the correct citation for the species name.